The Effect of Financial Behavior, Financial Literacy, and Financial Knowledge on Employee Financial Satisfaction at PT Birawa Eka Sapta Gresik - Jessica Novia Farhen; Anita Handayani (INNOVATION RESEARCH JOURNAL, 2022)
The background in this study based on the results of a pre-survey on financial satisfaction of employees of PT Birawa Eka Sapta Gresik showed dissatisfaction. This study aims to examine the effect of financial behavior, financial literacy, and financial knowledge on employee financial satisfaction at PT Birawa Eka Sapta Gresik. This study uses quantitative methods. The population in this study was the employees of PT Birawa Eka Sapta Gresik, amounting to 60 people, while the sample was taken using the Non Probability Sampling technique using a saturated sample. The reason is because the sampling of the population is less than 100. The sample studied by the researcher is 60 employees. The analysis technique uses instrument test, classical assumption test, and hypothesis testing. For the test tool, the Statistical Package for the Social Sciences (SPSS) is used. The results of this study indicate that financial behavior, financial literacy, and financial knowledge have a positive and significant effect on employee financial satisfaction.